Factors Affecting Fraud Prevention in Village Financial Management with Individual Morality As A Moderation Variable - Fitri, Ramadhani Arda; Nasir, Azwir; Basri, Yesi Mutia (Golden Ratio of Data in Summary, 2025)
The purpose of this study was to test and analyze the influence of organizational culture, internal locus of control and whistleblowing system on fraud prevention in village financial management with individual morality as a moderating variable. The population in this study were all village officials totaling 408 consisting of village heads, village secretaries, and village treasurers who work in village governments throughout Bengkalis Regency. Sampling using the census method, namely using the entire population as a research sample, the data used is primary data sourced from questionnaires. The data analysis technique used in this study is the SmartPLS 4 program. The results of this study indicate that organizational culture, internal locus of control and whistleblowing system have a positive and significant effect on fraud prevention in village financial management. Individual morality is able to moderate the influence of internal locus of control and whistleblowing system on fraud prevention in village financial management. While individual morality is unable to moderate the influence of organizational culture on fraud prevention in village financial management.